Understanding Commercial Free-Choice Mineral Mixes for Beef Cattle - Bob Myer; Travis Maddock; Lee McDowell (EDIS)
AN245, a 6-page fact sheet by Bob Myer, Travis Maddock, and Lee McDowell, discusses aspects of a good mineral program for beef cattle. Includes references. Published by the UF Department of Animal Science, July 2010.